(untitled) (Third Sector Social Economic Review, 2019)
In this article, high-rise and multi-storey buildings, which were revealed by many technical developments following the invention of cement and elevators in the eighteenth century, are examined. The tall buildings, first built in Western Europe and then in the United States, are now spread to almost all countries of the world. Buildings may be up to several-floors in the first years of the Republic of Turkey, has reached to 7-8 floors in the 1950s. The construction of multi-storey buildings in Turkey began with the construction of the Emek Office Block (Emek İşhanı) in 1965. In this article, Law of Buildings (Ebniyye Kanunu), the fist law related to high-rise buildings, enacted in 1864, “Municipal Building and Roads Law (Belediye Yapı ve yollar Kanunu)” in 1933, “Ankara City Reconstruction Guide (Ankara Şehri İmar Kılavuzu)” published in 1946, “Planned Areas Type Zoning Regulation (Planlı Alanlar Tip İmar Yönetmeliği)” dated 1985, “Metropolitan Municipality Law (Büyükşehir Belediyesi Kanunu)” dated 2004, and construction zoning laws and bylaws of Metropolitan and city municipalities will be elaborated, and the consequences of these laws will be discussed.